2007
DOI: 10.1074/jbc.m610948200
|View full text |Cite
|
Sign up to set email alerts
|

The Reversion-inducing Cysteine-rich Protein with Kazal Motifs (RECK) Interacts with Membrane Type 1 Matrix Metalloproteinase and CD13/Aminopeptidase N and Modulates Their Endocytic Pathways

Abstract: The reversion-inducing cysteine-rich protein with Kazal motifs (RECK) is anchored to the cell surface via glycosylphosphatidylinositol. This molecule antagonizes the function of membrane type 1 matrix metalloproteinase (MT1-MMP) to promote proMMP-2 maturation. Here, we attempt to clarify the mechanism underlying RECK functions. First, we found that RECK forms a complex with MT1-MMP and inhibits its proteolytic activity. Notably, RECK increases the amount of MT1-MMP that associates with detergent-resistant memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
83
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(86 citation statements)
references
References 41 publications
2
83
0
Order By: Relevance
“…Tumor cells were cultured in DMEM supplemented with 10% FCS. Transfection of HT1080 cells was described (16).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tumor cells were cultured in DMEM supplemented with 10% FCS. Transfection of HT1080 cells was described (16).…”
Section: Methodsmentioning
confidence: 99%
“…The product of this gene can directly bind to a series of metalloendopeptidases, including MMP-9 (9), MMP-2 (15), membrane type 1 (MT1)-MMP, CD13/ APN (16), and ADAM10 (17), and attenuate their proteolytic activity competitively in most of cases. Two metalloprotease substrate-like domains recently discovered in RECK may provide a structural basis for its biochemical actions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…RECK was first isolated as a transformation-suppressor gene by cDNA expression cloning (Noda et al, 1989;Takahashi et al, 1998) and found to encode a membraneanchored regulator of several extracellular metalloproteinases, including MMP2, MMP7, MMP9, MT1-MMP, ADAM10 and CD13 (Takahashi et al, 1998;Oh et al, 2001;Miki et al, 2007;Muraguchi et al, 2007;Omura et al, 2009). These proteases have been implicated in tissue remodeling and cleavage of various extracellular molecules under normal and pathological conditions (Sternlicht and Werb, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Reversion-inducing cysteine-rich protein with Kazal motifs (RECK) acts as a membrane-anchored metalloproteinase regulator [1][2][3][4] which functions as a regulator of extracellular matrix integrity in normal condition, contributing to tumor and metastasis suppressing agent. However, recent study found abundant expression of RECK in the cells associated with blood vessels undergoing rapid remodeling in the mouse implantation chambers, suggesting that RECK has a role in vascular remodeling which may involve non-sprouting mechanisms such as intussusception and pruning.…”
Section: Introductionmentioning
confidence: 99%